A cantilever-based NEM nonvolatile memory utilizing electrostatic actuation and vibrational deactuation for high-temperature operation - Gopal, Jayaraman Karthik (2015)
This paper proposes a cantilever-based nanoelectromechanical (NEM) nonvolatile memory (NVM) with a novel write scheme for reliable memory operation at very high-operating temperature (up to 300 °C) in rugged electronics. The memory bit (0/1) is formed by the opening/closing of a cantilever beam. Permanent retention is obtained by adhesive force between two smooth surfaces in contact, eliminating leakage observed in all types of storage-layer-based NVMs. This allows the proposed NEM memory structure to be implemented using a simple bilayer design and easily integrated with the CMOS platform with leakage of 144 pA, which is significantly less compared with SRAM. The experimental analysis of vibrational reset is reported for the first time in this paper. An array structure using the proposed NEM memory device and CMOS devices is presented. Each bit cell consists of one NEM memory device and one nMOS transistor for realizing full random-access operation.